Learning loss and recovery from the COVID-19 pandemic: A systematic review of evidence - Nina Ashley Dela Cruz; Ann Jillian Adona; Rhea Molato; Albert Park (Asian Development Bank (ADB), 2024)
This systematic review covers 56 studies that measure the effects of school closures on learning outcomes during the coronavirus disease (COVID-19) pandemic and 20 studies that evaluate the impact of measures to reduce learning loss. It restricts attention to evaluations with credible control groups and provides the first meta-analysis of learning losses that covers more developing countries (21) than developed ones (15). We find that a year of school closure is associated with learning loss equivalent to 1.1 years' worth of learning and that school reopening mitigates these losses down to 0.5 years. With regard to measures to reduce learning loss, we find that tutoring delivered either in-person or through mobile phones has positive, statistically significant effects on mitigating learning loss.
Keywords: I20; I21; I24; I28; 330; learning loss; COVID-19; education; systematic review; meta-analysis